Effect of Axial Compression Ratio on Seismic and Self-Centering Performance of Unbonded Prestressed Concrete Columns. (18th January 2022) - Shi, Yun; Yuan, Guanglin; Zhu, Hao
Abstract : To explore the influence of the applied axial compression ratio and preloaded axial compression ratio on the seismic performance of unbonded prestressed concrete columns, pseudo-static tests were carried out on four prestressed columns and one ordinary column in this study. The seismic performance indexes of test columns were studied and analyzed, including failure modes, hysteresis curves, skeleton curves, stiffness, ductility, and energy dissipation. The test results show that compared with concrete columns with ordinary reinforcement, the hysteresis curve of reinforced concrete columns with prestressed tendons has a pinch phenomenon to a certain extent, and the energy dissipation performance becomes worse. For the prestressed columns, the greater the applied axial compression ratio, the worse the fullness of hysteresis curves and the energy dissipation performance, the greater the residual displacement, the faster the strength attenuation, and the worse the self-centering performance. For the posttensioned unbonded prestressed concrete columns, the greater the preloaded axial compression ratio, the worse the energy dissipation performance of the test column, the slower the strength attenuation, and the better the self-centering performance.